Management and control of transparent optical networks. - Maeda, M.W (IEEE Journal on selected areas in communications)
Multiwavelength optical networking is expected to play a significant role in the next-generation transport networks providing capacity enhancements as well as built-in network survivability and reconfigurability. While advances have been made in the hardware technologies, considerable research effort is still required in the area of network management and control in order for optical networking to be proven commercially viable. This paper investigates key design issues concerning optical network management and control and examines how the networking architecture is influenced by the various management considerations